Inside the Toefl iBT
Due to a growing need for foreign language speakers to master English, more people than ever are taking the TOEFL (Test of English as a Foreign Language). As the publisher of the #1 bestselling TOEFL iBT guide, Kaplan offers this portable study aid for students on the go. With exam information, practice for every question type, and test-taking skills, Inside the TOEFL iBT is an inexpensive, easy-to-use guide that gives test takers the tools they need to achieve a high score on the Internet-based TOEFL. Includes: Important information about the interactive TOEFL iBT exam A vocabulary list with important words and definitions Focused practice for reading, writing, listening, and speaking Review of each question type Kaplan\\\\\\\'s proven score-raising strategies for basic and advanced topics